2019
DOI: 10.1634/theoncologist.2018-0505
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Activity of Nivolumab for Human Papilloma Virus-Related Juvenile-Onset Recurrent Respiratory Papillomatosis

Abstract: Background Juvenile‐onset recurrent respiratory papillomatosis (JO‐RRP) is a human papilloma virus‐mediated progressive benign neoplasm that affects children and young adults. Primary management consists of regular surgical debulking to maintain airway patency and vocal function. Like condyloma acuminata, JO‐RRP is associated with immune dysregulation, and T cells isolated from papillomas express an anergic phenotype. Therefore, we hypothesized that programmed death protein 1 axis inhibition could stabilize tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Juvenile-onset recurrent respiratory papillomatosis (JORRP), primarily caused by low-risk HPV6 and HPV11 infection, is considered as the most common benign laryngeal tumor in children that manifests with hoarseness and loss of voice ( 4 ). Moreover, repeated costly surgical interventions place a lifetime disease burden on families ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Juvenile-onset recurrent respiratory papillomatosis (JORRP), primarily caused by low-risk HPV6 and HPV11 infection, is considered as the most common benign laryngeal tumor in children that manifests with hoarseness and loss of voice ( 4 ). Moreover, repeated costly surgical interventions place a lifetime disease burden on families ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple endolaryngeal procedures can lead to glottis synechia and irreversible damage to the vocal cords as well as impaired social life ( 22 ). To improve the surgical outcome and extend symptom-free periods, numerous adjuvant treatments have been tried: interferon α ( 23 ), celecoxib ( 24 ), bevacizumab ( 25 ), cidofovir ( 26 , 27 ), PD-1/PD-L1 immunotherapy ( 28 , 29 ), and the quadrivalent HPV vaccine ( 30 ). At the time of writing, none of these treatments have been recommended for routine use by the International Pediatric Otolaryngology Group ( 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…At the time of writing, none of these treatments have been recommended for routine use by the International Pediatric Otolaryngology Group ( 31 ). The most promising ones are the quadrivalent HPV vaccine, bevacizumab and PD-1/PD-L1 immunotherapies which appear to decrease relapses ( 28 , 29 , 32 , 33 ).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple endolaryngeal procedures can lead to glottis synechia and irreversible damage to the vocal cords, as well as an impaired social life [ 23 ]. To improve the surgical outcome and extend the symptom-free interval, numerous adjuvant treatments have been tried: interferon α [ 24 ], celecoxib [ 25 ], bevacizumab [ 26 ], cidofovir [ 27 , 28 ], PD-1/PD-L1 immunotherapy [ 29 , 30 ] and the quadrivalent HPV vaccine [ 31 ]. Currently, routine use of these treatments is not recommended by the International Pediatric Otolaryngology Group [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, routine use of these treatments is not recommended by the International Pediatric Otolaryngology Group [ 32 ]. The most promising approaches are the quadrivalent HPV vaccine, bevacizumab and PD-1/PD-L1 immunotherapies which appear to decrease relapses [ 29 , 30 , 33 , 34 ]. Systemic bevacizumab, a monoclonal antibody against VEGF-A, seems to be the most promising treatment for aggressive forms of JoRRP, as several studies found a rapid and sustained partial or complete response to treatment in patients with lung involvement [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%